2015
DOI: 10.1515/jlecol-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Czech Methodology of Biogeographical Landscape Differentiation in Geobiocoenological Concept – Examples from Cuba, Tasmania and Yemen

Abstract: Within the area of Central Europe, and especially in the Czech Republic (and former Czechoslovakia), geobiocoenological landscape differentiation has been applied for more than 40 years to create a spatial model of the natural (potential) condition of geobiocoenoses in the landscape. Because long-term objective of geobiocoenology is to contribute to the creation of harmonic cultural landscape by gradual development of a comprehensive system of groundworks for sustainable landscape use, and as Mendel University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Net migration, calculated as the mean value for the period 1996-2007, is understood as a proxy of the quality of life (see, e.g., Navarro-Azorín and Artal-Tur, 2015). The coeffi cient of ecological stability expresses the ratio between environmentally stable and environmentally unstable land-use categories (see, e.g., Buček et al, 2015). This indicator refers to the year 2007.…”
Section: Data -Explanatory and Control Variablesmentioning
confidence: 99%
“…Net migration, calculated as the mean value for the period 1996-2007, is understood as a proxy of the quality of life (see, e.g., Navarro-Azorín and Artal-Tur, 2015). The coeffi cient of ecological stability expresses the ratio between environmentally stable and environmentally unstable land-use categories (see, e.g., Buček et al, 2015). This indicator refers to the year 2007.…”
Section: Data -Explanatory and Control Variablesmentioning
confidence: 99%
“…There were no days with the zero daily flow from the SE stem indicating C3 type of photosynthesis in D. cinnabari although Brown and Mies (2012) reported that facultative Crassulacean Acid Metabolism (CAM) might occur in this plant. Nevertheless, we realize, that to talk about CAM in D. cinnabari, synchronous photosynthetic measurements should be provided and longer (at least one year) period of Fig.…”
Section: Relationships Between Sap Flow In the Stem And In The Roots mentioning
confidence: 97%
“…The sample plant was growing in the open space on the limestone plateau, characterized by karstic features (Brown and Mies 2012) (Fig. S1).…”
Section: Sample Plant and Study Area Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of TSES is that it addresses one of the key GI conceptsconnectivity. It is an ecological network (Buček et al, 2012), based on biogeographical landscape differentiation in geobiocoenological conception (Buček et al, 2015), which secures physical links among habitats, ensuring uninterrupted movement of organisms and is similar to other ecological networks in Europe, e.g. Germany (Jedicke, 1994), Slovakia (Topercer, 2013) or Netherlands (Lammers & Zadelhof, 1996).…”
Section: Introductionmentioning
confidence: 99%